STRATEGI PEMASARAN SYARIAH BAKSO MUSTOFA KRAKSAAN PROBOLINGGO - Abdul Choliq (IZZI: Jurnal Ekonomi Islam, 2023)
The business of being a meatball seller is one of the businesses engaged in fast food processing. This business is also a very popular food for the people of Indonesia. Therefore, I am interested in implementing a trader's marketing strategy to increase the level of welfare of the families of meatball traders in Kraksaan District, Probolinggo Regency. ), marketing strategy is a form of a directed plan in the field of marketing to obtain an optimal result, strategy and marketing from the point of view of the seller (4P) is a strategic place (place), quality product (product), competitive price (price) and vigorous promotion. First, at the beginning of making Pak Tapa's meatballs, he followed the recipe of his parents, who used to sell meatballs in the Kraksaan area. After that he tried to apply the knowledge he got from his parents about making meatballs himself and starting a business on January 10, 2010. Before starting a meatball business. Mr. Tapa once worked in a rice field in Kalibuntu, Kraksaan sub-district, Probolinggo Regency, but he was willing to leave his job due to opening and pursuing a meatball business, which his own parents had taught him from the start.